PENERAPAN MANAGING CHANGE PADA PERGANTIAN PEMIMPIN DI PT BFI FINANCE, TBK– CABANG SURABAYA 2 - Permadi, Edo Galih (Fakultas Ekonomi Universitas Wisnuwardhana, 2021)
Abstract:In organizations and companies, changes often occur with the aim of improving business processes within the organization. When changes occur within the organization, it is not uncommon for resistanceto occur from the organization's employees. These changes can be in the form of a change of leaders in the company. This happened at PT BFI Finance Tbk second Surabaya branch when there was a change of Branch Manager. Effective change management is needed to facilitate the changes. Activities that can be carried out to produce effective change management are Motivating Change and Managing the Transition. This study aims to determine the application of Motivating Change and Managing the Transition and its impact on the change of leaders at PT BFI Finance Tbk second Surabaya branch. This research is a qualitative descriptive study using observations and interviews (in-depth interviews) to collect research data. Based on the research results, the application of Motivating Change and Managing the Transition in the change of leaders at PT BFI Finance Tbk Surabaya branch 2 assist the change efforts made by the new Branch Manager so as to reduce employees’resistance. Keywords: BFI Finance, managing change, Motivating Change, Managing the Transition, change of leadership